Design of a Decision Tree-Based Decision Support System in Predicting the Causes and Handling of ABO Blood Group Discrepancies - Indriputri, Cut; Maulana, Reza (Jurnal INSYPRO (Information System and Processing), 2023)
Blood type discrepancies occur when there is a difference between the expected blood type examination results and the results actually found. This can be a serious problem in the context of medical care, especially if it occurs in situations requiring blood transfusions or organ transplants. Mistakes in determining a patient’s or potential donor’s blood type can result in dangerous transfusion reactions or organ transplant rejection. This research discusses the design of a decision tree-based decision support system in predicting the causes and treatment of ABO blood group discrepancies. The research begins by describing the discrepancies scenario that occurs and the patient’s condition, then considering and predicting the possibility, type of discrepancy, causes, treatment, and the actual blood type which is outlined in a decision tree. Based on the results of the discrepancies scenario analysis, the design of a decision tree-based decision support system contains several categories of nodes, including the examination results as the root node; conditions and scenarios as decision nodes, and leaf nodes as final results which include predicted results, such as causes, actual blood type, as well as types of discrepancies and their treatment. A decision support system based on a decision tree can help predict the causes and treatment of ABO blood group discrepancies quickly and accurately. It is hoped that this research will continue to the implementation stage.